iTRAQ-Based Comparative Proteomic Analysis of Adult Schistosoma japonicum from Water Buffalo and Yellow Cattle - Zhai, Qi (Front Microbiol, 2018)
Schistosomiasis japonicum is one of the most severe zoonotic diseases in China. Water buffalo and yellow cattle are important reservoir hosts and the main transmission sources of Schistosoma japonicum in endemic areas. The susceptibility of these two hosts to schistosome infection is different, as water buffaloes are less susceptible to S. japonicum than yellow cattle. In this study, iTRAQ-coupled LC-MS/MS was applied to compare the protein expression profiles of adult schistosomes recovered from water buffalo with those of yellow cattle. A total of 131 differentially expressed proteins (DEPs) were identified, including 46 upregulated proteins and 85 downregulated proteins. The iTRAQ results were confirmed by Western blotting and quantitative real-time PCR. Further analysis indicated that these DEPs were primarily involved in protein synthesis, transcriptional regulation, protein proteolysis, cytoskeletal structure and oxidative stress response processes. The results revealed that some of the differential expression molecules may affect the development and survival of schistosomes in these two natural hosts. Of note, this study provides useful information for understanding the interplay between schistosomes and their final hosts.